Severity of Maxillofacial Trauma in Motor Bike Riders among Helmet Wearers vs. Non-Helmet Wearers - Shehryar Alam Khan, Gulraiz Zulfiqar, Shahzada Faiz Ahmad Khan, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To evaluate the severity of maxillofacial trauma in motorbike riders among helmet wearers and non-helmet wearers. Study Design: A cross-sectional study was conducted. The setting was Jinnah Hospital Lahore from April 1, 2021, to October 1, 2021. Method: The study was conducted at Jinnah Hospital Lahore from April 1, 2021, to October 1, 2021. The sample size of our study was 143 patients. The data were collected from the clinical records of individuals who had suffered maxillofacial trauma. Subjects engaged in motorcycle accidents with thorough case records and radiological studies met the inclusion criteria. The collected data were analyzed using the SPSS 23 version. Results: In our study, the mean age of patients was 31.10±9.15, with 129 (90.2%) patients being male and 14 (9.8%) patients being female. 41 (28.5%) patients were helmet users, and 102 (71.3%) patients were non-helmet users. In our study, we also found the severity of maxillofacial trauma: 39.2% of patients had mandible fractures, 35.7% had zygomatic arch fractures, 65.7% had soft-tissue injuries, and 21.0% had dentoalveolar fractures. Observed the greater severity of maxillofacial trauma in non-helmet users with a significant p value (p<0.05). Non-helmet wearers noted more general comminuted fractures, loss of organs like blindness and loss of vision due to orbital fractures, more deep facial lacerations causing lifetime esthetic concerns, a greater hospital stay, and more expenditure at the hospital. Also, more trauma to teeth and injuries lead to a more expensive burden for tooth prostheses afterwards. In helmet wearers, there were fewer fractures, and patients had to stay less or didn’t need to stay at the hospital; they could continue with their daily routine work and job. Practical Implication: Helmet usage requirements must be carefully enforced, and public awareness about motorcycle safety must be encouraged. Conclusion: In our study, we concluded that there was a significant difference in the severity of maxillofacial trauma in motorbike riders between helmet wearers and non-helmet wearers. These fractures may be avoided by encouraging the use of safety equipment (such as required crash helmet usage), strengthening road infrastructure, and limiting the number of motorbikes registered. Helmet usage requirements must be carefully enforced, and public awareness about motorcycle safety must be encouraged. Keywords: Severity, maxillofacial trauma, motor bike, helmet wearers, Non-Helmet wearers